Use of Social Media Among Youth: The Reflection of Structuration Theory - Rawal, Sunil (Patan Prospective Journal, 2022)
The research reveals the views of youngsters on the usage of social media. The use of social media by youngsters has grown in popularity in contemporary society. The study performed a targeted questionnaire survey with high school, undergraduate, and graduate students from various public and private educational institutions to better understand the role that social media platforms play in the lives of young people and how they utilize them. Anthony Giddens' structuration theory, which stresses the effect of social systems on individual behavior, served as the study's theoretical foundation. The study's findings revealed that individual agency (young people's interests and motives for using social media) and structures (such as accessible platforms and the laws and norms regulating their usage) shape and impact each other in the use of social media by youth. Young people must be informed of the possible advantages and hazards of social media and utilize it properly. We expect that this research will add to a better understanding of the influence of social media on young people's communication, relationships, and general well-being.